Changes in Obesity Phenotype Distribution in Mixed-ancestry South Africans in Cape Town Between 2008/09 and 2014/16 - Davids, Saarah Fatoma; Matsha, Tandi Edith; Peer, Nasheeta; Erasmus, Rajiv Timothy; Kengne, Andre Pascal (Frontiers in Endocrinology, 2019)
Background: Evidence is needed on the changes in obesity phenotypes in African populations and its effects on the development of non-communicable diseases. We investigated changes in obesity phenotype from 2008/09 to 2014/16 in the mixed-ancestry population of Bellville South in Cape Town, South Africa. Methods: In all, 928 (2008/09) and 1969 (2014/16) participants aged >20 years were included in two community-based cross-sectional studies. For obesity phenotype classification a combination of body mass index (BMI) categories and prevalent cardiometabolic disease risk factors were used, with the presence of two or more cardiometabolic abnormalities defining abnormal metabolic status. Interaction tests were used to investigate changes in their distribution across years of the study. Results: The distribution of BMI categories differed significantly between the two years; normal weight, overweight and obese: 27.4%, 27.4% and 45.3% in 2008/09 vs. 34.2%, 23.6% and 42.2% in 2014/16 (p-value=0.001). There was no differential effect in the distribution of obesity phenotypes pattern across the two time-points (interaction p=0.126). Across BMI categories, levels of cardiometabolic risk factors linearly deteriorated in both metabolic healthy and abnormal participants (all p≤0.018 for linear trends). Findings were not sensitive to the number of metabolic abnormalities included in the definition of obesity phenotypes. Conclusions: Our study has shown negligible differences in obesity phenotypes over time in this population, but high burden of metabolic abnormalities among normal weight participants, and a significant proportion of metabolically healthy obese individuals. These observations need further investigations in order to improve risk stratification and reduction strategies for obesity phenotypes